Coupled Reynolds–Mach–Thermal Dynamics in Vortex-Stabilized Meso-Scale Combustors: Implications for Efficiency and Stability - Azri Hariz Roslan; Mohd Nawi, Mohd Al-Hafiz; Mohd Sharizan Md Sarip; Chu Yee Khor; Muhammad Lutfi Abd Latif; Mohammad Azrul Rizal Alias; Mohd Fathurrahman Kamarudin; Hazrin Jahidi Jaafar; Mohd Danish (International Journal of Integrated Engineering, 2026)
Meso-scale combustors have unique thermo-fluid challenges due to a high surface-to-volume ratio. Small changes in Reynolds number (Re) and Mach number (Ma) can have a big effect on how vortices behave, how heat moves, and how stable flames are. This study looks at how mass flow rate, Re, and Ma work together to change the temperature distribution in two vortex-stabilized combustor setups with different volumes. Current study works on high-fidelity CFD simulations using the RNG k–ε turbulence model with eddy dissipation chemistry over Re = 301.4–1153.8 (Ma<0.3), which stands for incompressible subsonic regimes. The results show that Re and Ma are directly proportional when the geometry and fluid properties stay the same. This makes it possible to predict how thermal fields will change with size. The larger-volume combustor always had stronger swirl and more coherent central recirculation zones (CRZs), which made the flame zones wider, improved radial heat transfer, and cut down on heat losses through the walls in all operating conditions. On the other hand, the compact combustor broke down vortices quickly, had steep radial temperature gradients, and was more likely to have flames put out at high Re. The results show a linked Re–Mach–temperature relationship that improves our ability to predict meso-scale combustion. This gives us a design framework to improve the stability, efficiency, and durability of portable power generation and micro-propulsion systems.